2023
DOI: 10.18332/popmed/174287
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of electronic cigarette smoking among university students in the West Bank: Practice, motivation, and dependence of a new emerging hazard

Muhyee E. Jaber,
Laith Nouri,
Alaa Hamed
et al.

Abstract: INTRODUCTION Tobacco smoking has reached an alarming rate among the young Palestinian population, specifically university students. Electronic cigarettes or e-cigarettes, are an emerging hazard in the West Bank. However, the epidemiology of e-cigarette smoking among Palestinians is poorly described. Therefore, we aimed to determine the prevalence, pattern, motivation, dependence, and readiness to quit e-cigarette smoking among male university students. METHODS In 2022, face-to-face interviews were conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Other studies revealed that waterpipe smoking was more common among males, younger age groups, those with a lower education level 12,13 and as an alternative to cigarettes smoking 15 . A recent study in 2023 described the epidemiology of e-cigarette smoking among Palestinians and indicated that e-cigarette smoking is prevalent among university students (13.3%) 16 , while the PCBS indicated that 4% of individuals aged ≥18 years in the West Bank were e-cigarette smokers 11 . Another study reported a high prevalence of tobacco smoking among Palestinian refugee men and linked their use with eating behaviors and obesity 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies revealed that waterpipe smoking was more common among males, younger age groups, those with a lower education level 12,13 and as an alternative to cigarettes smoking 15 . A recent study in 2023 described the epidemiology of e-cigarette smoking among Palestinians and indicated that e-cigarette smoking is prevalent among university students (13.3%) 16 , while the PCBS indicated that 4% of individuals aged ≥18 years in the West Bank were e-cigarette smokers 11 . Another study reported a high prevalence of tobacco smoking among Palestinian refugee men and linked their use with eating behaviors and obesity 17 .…”
Section: Introductionmentioning
confidence: 99%